The effects of using lime and styrene–butadiene–styrene on moisture sensitivity resistance of hot mix asphalt - Kök, Baha Vural; Yılmaz, Mehmet (My University, 2009)
This study focuses on determining the effects of styrene–butadiene–styrene (SBS) and using mineral ?ller with lime on various properties of hot mix asphalt especially moisture damage resistance. The asphalt cement was modi?ed with 2%, 4% and 6% SBS. The lime treated mixtures containing 2% lime by weight of the total aggregate as ?ller. The physical and mechanical properties of polymer modi?ed binder and binder–aggregate mixes were evaluated through their fundamental engineering properties such as dynamic shear rheometer (DSR), rotational viscosimeter (RV) for binders, Marshall stability, stiffness modulus, indirect tensile strength and moisture susceptibility for mixes. The retained Marshall stability (RMS) and tensile strength ratio (TSR) values were calculated to determine the resistance of mixtures to moisture damage. To investigate clearly the effective of SBS and lime seven freeze–thaw cycle was applied to specimens at TSR test. The results indicate that application of SBS modi?ed binders and lime as mineral ?ller one by one improves the stability, stiffness and strength characteristic of hot mix asphalt. According to retained Marshall stability it is concluded that addition of only 2% lime have approximately same effect with addition of 6% SBS. Using lime together within the SBS modi?ed mixes exhibit high accordance and exacerbates the improvement of properties. Specimens containing both 2% lime and 6% SBS, have the highest stiffness modulus which is 2.3 times higher than those of the control mixture and showed the least reduction in tensile strength ratio while maintaining 0.70 tensile strength ratio after seven freeze–thaw cycle.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Moisture damage; Modified bitumen; Lime; Retained Marshall stability; Indirect tensile strength